Tinjauan Ekonomi Syariah tentang Proyeksi Penerimaan dan Penggunaan Wakaf pada Wakaf Daarut Tauhiid - Camila Afiyanti; M. Roji Iskandar; Ifa Hanifia Senjiati (Bandung Conference Series: Sharia Economic Law, 2022)
Abstract. Based on the results of preliminary observations, that the nominal amount of revenue, use and balance in Daarut Tauhiid waqf management activities in 2015-2019 shows a fluctuating development trend. Overall data on the number of receipts showed an increase until 2018, and in 2019 showed a declining trend. The usage graph is relatively stable and shows an increasing development every year. In contrast to receipts and usage charts, charts for balances show unpredicable (unpredictable) developments. The balance in 2015 to 2016 showed a decrease, then rose to the following years and reached the highest curve in 2018. The balance for 2019 showed a very significant decline.The type of research used is descriptive method with a qualitative approach. The data needed from this study are primary data (interviews with waqf managers) and secondary data (recap documents of DT Waqf activity reports in 2015-2019). As for managing data, the author uses a qualitative research type that is descriptive analysis. In accordance with the title of the study, the analysis used is "trend analysis" (Least Square calculation formula).From the analyzed data, it can be concluded: (a) Waqf at Daarut Tauhiid waqf is in line and in accordance with the provisions of the principles of Islamic Economics management, (b) acceptance and use of waqf at Daarut Tauhiid waqf in Bandung for the 2015-2019 period, showing fluctuating conditions. Nominal amount of revenue shows a significant increase, the average annual revenue is Rp. 28,474,115,196, the average usage every year is Rp. 24.007.086.199.11. The nominal amount of the balance from 2015-2019 shows a fluctuating number. (c) projection of waqf revenue and use at Daarut Tauhid waqf until 2025. The average increase in revenue is Rp. 3.862944 every year. The average increase in usage is Rp. 3,806,191 every year. Based on the conclusions above, it is recommended: (a) The actors (waqf managers) should know the problems of sharia economic law, especially the legal basis and principles of its management so that they can be farthest from things that are prohibited by religion, (b) the Nazirs in accepting and using waqf funds honestly in accordance with the stipulated provisions, (c) waqf managers should continue to conduct analyzes of the public's understanding of Productive and Cash Waqf. Abstrak. Berdasarkan hasil pengamatan pendahuluan, bahwa jumlah nominalpenerimaan, penggunaan dan saldo pada aktivitas pengelolaan wakaf Daarut Tauhiid tahun 2015-2019 menunjukan trend perkembangan yang fluktuatif. Secara keseluruhan data jumlah penerimaan menunjukkan peningkatan sampai tahun 2018, dan tahun 2019 menunjukkan trend menurun. Grafik penggunaan relatif stabil dan menunjukkan perkembangan yang meningkat setiap tahunnya. Berbeda dengan grafik penerimaan dan penggunaan, grafik untuk saldo menunjukkan perkembangan yang unpredicable (tidak dapat diprediksikan). Dari saldo pada tahun 2015 ke tahun 2016 menunjukkan penurunan, kemudian naik ke tahun tahun berikutnya dan mencapai kurva tertinggi tahun 2018. Saldo untuk tahun 2019 menunjukkan penuruan yang sangat signifikan. Jenis penelitian yang digunakan adalah metode deskriptif dengan pendekatan kualitatif. Data yang diperlukan dari penelitian ini adalah data primer (wawancara dengan pengelola wakaf) dan data sekunder (dokumen rekap laporan aktivitas Wakaf DT tahun 2015-2019). Adapun dalam mengelola data penulis menggunakan jenis penelitian kualitatif yang bersifat deskriptif analisis. Sesuai dengan judul penelitian, maka analisis yang digunakan adalah “analisis trend” (Rumus perhitungan Least Square). Dari data yang dianalisis dapat ditarik kesimpulan: (a) Wakaf pada wakaf Daarut Tauhiid sudah sejalan dan sesuai dengan ketentuan pada prinsip prinsip pengelolaan Ekonomi Syariah, (b) penerimaan dan penggunaan wakaf pada wakaf Daarut Tauhiid Bandung periode 2015-2019, menunjukkan kondisi yang fluktuatif. Jumlah Nominal penerimaan menunjukkan peningkatan yang signifikan, rata rata penerimaan setiap tahunnya sebesar Rp. 28.474.115.196, rata rata penggunaan setiap tahun sebesar Rp. 24.007.086.199,11. Jumlah nominal saldo dari tahun 2015-2019 menunjukkan angka yang fluktuatif. (c) proyeksi penerimaan dan penggunaan wakaf pada wakaf Daarut Tauhiid sampai dengan tahun 2025. Rata rfata kenaikan penerimaan sebesar Rp. 3.862944 setiap tahun. Rata rata kenaikan penggunaan sebesar Rp. 3.806.191 setiap tahun. Berdasarkan kesimpulan di atas, disarankan : (a) Para pelaku (pengelola wakaf) hendaknya mengetahui masalah hukum ekonomi syari’ah terutama dasar dasar hukum dan prinsip prinsip pengelolaannya sehingga bisa terjauh dari hal-hal yang di larang oleh agama, (b) para Nazir dalam melakukan penerimaan dan penggunaan dana wakaf dengan jujur sesuai dengan ketentuan ketentuan yang ditetapkan, (c) para pengelola wakaf hendaknya terus melakukan analisis-analisis tentang pemahaman masyarakat terhadap Wakaf Produktif dan Uang.